TNF-α Increases Production of Reactive Oxygen Species through Cdk5 Activation in Nociceptive Neurons - Sandoval, Rodrigo; Lazcano, Pablo; Ferrari, Franco; Pinto-Pardo, Nicolás; González-Billault, Christian; Utreras, Elías (Frontiers in Physiology, 2018)
The participation of reactive oxygen species (ROS) generated by NOX1 and NOX2/NADPH oxidase has been documented during inflammatory pain. However, the molecular mechanism involved in their activation is not fully understood. We reported earlier a key role of Cyclin-dependent kinase 5 (Cdk5) during inflammatory pain. In particular, we demonstrated that TNF- increased p35 expression, a Cdk5 activator, causing Cdk5-mediated TRPV1 phosphorylation followed by an increment in Ca2+ influx in nociceptive neurons and increased pain sensation. Here we evaluated if Cdk5 activation mediated by p35 transfection in HEK293 cells or by TNF- treatment in primary culture of nociceptive neurons could increase ROS production. By immunofluorescence we detected the expression of catalytic subunit (Nox1 and Nox2) and their cytosolic regulators (NOXO1 and p47phox) of NOX1 and NOX2/NADPH oxidase complexes, and their co-localization with Cdk5/p35 in HEK293 cells and in nociceptive neurons. By using a hydrogen peroxide sensor, we detected a significant increase of ROS production in p35 transfected HEK293 cells as compared with control cells. This effect was significantly blocked by VAS2870 (NADPH oxidase inhibitor) or by roscovitine (Cdk5 activity inhibitor). Also by using another ROS probe named DCFH-DA, we found a significant increase of ROS production in nociceptive neurons treated with TNF- and this effect was also blocked by VAS2870 or by roscovitine treatment. Interestingly, TNF- increased immunodetection of p35 protein and NOX1 and NOX2/NADPH oxidase complexes in primary culture of trigeminal ganglia neurons. Finally, the cytosolic regulator NOXO1 was significantly translocated to plasma membrane after TNF- treatment and roscovitine blocked this effect. Altogether these results suggest that Cdk5 activation is implicated in the ROS production by NOX1 and NOX2/NADPH oxidase complexes during inflammatory pain.